Avaliação das atividades antimicrobiana, antimalárica e inibitória da enzima acetilcolinesterase de Arrabidaea chica (Bignoniaceae) - Bêdo, Taís Rocha de Freitas Oliveira (2010)
Arrabidaea chica (Humb.& Bonpl.) belongs to Bignoniaceae, which comprises 113 genera and 800 species of shrub, trees, and lianas. The species of this taxon are distributed all over the tropical regions of the world and they frequently occur in the Americas. A. chica is popularly knows as "carajurú, capiranga, cipó-cruz, grajirú, crajurú, crajiru, guarajurupiranga, pariri, piranga, calajouru, karajura, and krawiru”. It is largely found in South America, mainly in the Amazon region. In folk medicine, the aqueous extract of its leaves is employed as an anti-inflammatory agent, and it finds application in wound asepsis and in the treatment of intestinal disorders, diarrhea, and leucorrhea, which accounts for the importance of studies on its chemiscal and biological properties. The aim of this work was to evaluate the antimicrobial, antimalarial, and acethylcolinesterase inhibitory activities of the crude ethanolic extract of A. chica and its fractions (Fr-1-Fr-4). Regarding the heme polymerization assay, fractions Fr-3 and Fr-4 furnished the best inhibitory perspectives. However, the fact that the results were obtained at tenfold the standard concentration shows that these fractions are not quantitatively promising. The crude extract and fractions (Fr-1-Fr4) displayed no inhibitory activity against acethylcolinesterase in the TLC assay. The MIC (Minimum Inhibitory Concentration) values were evaluated against the microorganisms Haemophilus influenzae, Staphilococcus aureus, Streptococcus pneumoniae, Streptococcus pyogenes, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae. The crude extract exhibited moderate antimicrobial activity (MIC= 300 µg/mL) against S. pneumoniae. The phytochemistry study of the hexane fraction (Fr-1), which moderately inhibits the growth of S. pneumoniae (MIC= 200 µg/mL), allowed identification of the compounds ethyl palmitate, ethyl octadec-9-enate, ethyl stearate, and squalene. The antimicrobial activity of Fr-1 should be correlated to the presence of ester of fatty acids, as identified by GC-MS. The EtOAc fraction (Fr-2), which displayed moderate antimicrobial activity against S. pneumoniae and H. influenzae (MIC= 300 µg/mL), was submitted to a Chromatographic Column. This procedure resulted in the subfraction 9 (SUBFR-9), which inhibited the growth of S. pneumoniae (MIC = ≤ 20 µg/mL) very satisfactorily. SUBFR-9 contains ursolic (1) and oleanolic (2) acids, which is the first report of these compounds in A. chica. The MIC values obtained for the isolated compounds 1 and 2 against S. aureus and S. pyogenes revealed an increase in the biological activity, demonstrating that the purification process caused such enhanced activity. Nevertheless, the MIC values against S. pneumoniae showed that the triterpenes 1 and 2 have the same activity independent of acting together in a mixture or in isolation after purification. Taken together, all the achieved data confirm the activity of SUBFR-9, and that 1 and 2 are the bioactive metabolites responsible for the activity of the subfraction. In conclusion, A. chica can be applied as an antimicrobial agent. Keywords: Arrabidaea chica, antimicrobial, acethylcolinesterase, malaria.